(untitled) (KSV Journal of Pharmacy and Health Sciences, 2025)
Medicine administration is influenced and affected by demographic, social, and practical factors such as dosage form characteristics, swallowing difficulties, posture, and patient awareness. These behaviours directly influence adherence and therapeutic success. Therefore, this study assesses the factors influencing medicine administration behaviour and purchasing practices among residents of Gandhinagar district. A cross-sectional study was conducted in two community pharmacies of Gandhinagar district, Gujarat, India. Total of 663 participants were recruited using convenience sampling. Data were collected through a structured questionnaire on demographics, and medicine administration behaviours. Descriptive statistics and chi-square tests were applied to determine associations. Most respondents (81.6%) swallowed tablets whole, 97.7% used water, and 58.4% experienced no swallowing difficulties. However, 41.6% reported problems such as throat discomfort and choking sensation. Posture and head position were significantly associated with ease of swallowing (p < 0.05). Demographic variables including age and education level showed associations with administration practices. Medicine administration behaviour is shaped by demographic and practical factors. Patient education on correct swallowing techniques, adequate liquid intake, and safe posture may enhance adherence. Pharmacists play a pivotal role in guiding community members toward rational medicine administration.